Differential clinical characteristics and performance of home antigen tests between parents and children after household transmission of SARS-CoV-2 during the Omicron variant pandemic. (March 2023) - Chen, Szu-Han; Wu, Jhong-Lin; Liu, Yun-Chung; Yen, Ting-Yu; Lu, Chun-Yi; Chang, Luan-Yin; Lee, Wang-Tso; Chen, Jong-Min; Lee, Ping-Ing; Huang, Li-Min
Highlights: Children had a lower COVID-19 vaccination rate and a higher transmission rate. Children with COVID-19 had more fever and higher peak fever than adults. The home rapid antigen test had a suboptimal negative predictive rate in children. The cycle threshold value of those with false-negative antigen tests was lower in children. Abstract: Objectives: The SARS-CoV-2 Omicron variant pandemic struck Taiwan in April 2022. Rapid antigen tests (RATs) play an important role in providing rapid results during a pandemic. However, self-collected samples by the children's caregivers without the supervision of medical personnel raise some concerns. Methods: This study was performed to investigate household transmission, clinical characteristics, and antigen performance in a special COVID-19 family clinic in a children's hospital. The performance of at-home RATs was evaluated based on reverse transcription-polymerase chain reaction. Results: We included 627 patients in our study between May 11 and June 10, 2022. The COVID-19 full vaccination rate was significantly higher in adults (98.5%) than in children (5.9%, P <0.001). The transmission rate was significantly higher in children (91.3%) than in adults (76.6%, P <0.001). Infected children had more incidents of fever (82.4% vs 22.4%, P <0.001) and a higher peak fever than adults. Based on the reverse transcription-polymerase chain reaction, the negative predictive rate of the home RAT was only 38.7% (95% confidence interval: 31.9-46.0%) in children. The cycle threshold value of those with false-negative antigen tests was significantly lower in children. Conclusion: Children had a higher transmission rate, more fever, and higher peak fever than adults. Home RAT has a suboptimal negative predictive rate in children. Graphical abstract: Image, graphical abstract